Phenomenon of fruit cracking, causes, and methods of control (Damascus University Journal of agriculture sciences, 2025)
Fruit cracking is one of the most important main reasons that lead to serious economic losses due to damage to the fruits and increased susceptibility to fungal and bacterial infections ، Fruit cracking often results from sudden and rapid growth of the fruit. Phenomenon of fruit cracking is often linked to excessive irrigation of water and thus its rapid absorption by the plant. This phenomenon may occur due to changes in environmental conditions, such as changing from cold weather and high humidity to hot and dry weather. Many factors contribute to avoiding this phenomenon, including regular irrigation and balanced fertilization, especially with calcium, as well as planting crack-resistant varieties and using growth regulators and transpiration inhibitors to reduce this phenomenon.
Keywords: Fruit Cracking; Mineral Nutrition; Growth Regulators; Physiological Disorders